Employee Empowerment in Nursing - Fatma Er; Serap Altuntaş (Association of Nurse Managers, 2015)
Employee empowerment is a strategy enabling employees to make decisions about their jobs, to feel enthusiastic and to conduct efforts in accordance with their institutions they work for, depending on cooperation, sharing and mutual confidence. Empowering employee means transferring of power for administrators; whereas for the employees, it means getting the power of making decisions within certain limits. The issue of 'employee empowerment' has also gained importance in health as in other sectors to provide an effective nursing service under contemporary conditions which are rapidly changing and developing due to competition, globalization and alteration in expectations of service fields. In order to have modern organizations working effectively, it is crucial to have employees who are empowered and dedicated to their institutions. Nurses should be given more autonomy to serve effectively and efficiently. Moreover, they must make decisions on their own in occupational issues, as well, which means they should be empowered. Empowerment of nurses has positive sides concerning personal and corporate development and patient care as well. Empowered nurses take responsibility of their work. Taking initiative solves problems and conflicts. This increases the employee's efficiency in the institution. An empowered working condition will be useful in controlling of nursing implementations, increasing organizational dependence, job efficiency, performance, satisfaction and motivation, decreasing rate of leaving from job and providing affirmative patient care outputs. High ranking nurses should include nurses in decision-making and performance evaluation processes and create opportunities of self-development and education. They should also help the nurses get access to necessary sources to actualize their works and encourage them to autonomously behave by giving them power and responsibility.